THE USA PRESIDENTIALISM AS THE REPRESENTATION OF THE AMERICAN POLITICAL CULTURE EVOLUTION - Lepska, Nataliia; Parkhomenko, Mariia (Fırat University, 2021)
The United States of America is a unique state with an unprecedented history and leadership policy, being a worldwide sight to behold. The USA aptitude for influencing vast problem solving, overcoming global conflicts, forming coalitions and setting the world’s agenda is trailblazing. However, many rigors the country has faced, it has always been able to hold a senior exterior position and to keep its political interior balance. The research aims to determine the essence of American political culture and trace the key aspects throughout U.S. history by analyzing the inaugural addresses of ten American presidents: G. Washington, J. Monroe, J. K. Polk, A. Lincoln, W. Wilson, F. D. Roosevelt, J. F. Kennedy, R. Reagan, B. Obama and D. Trump. Their presidential terms reflect different periods of the American historical process, where the important events happened in the United States. In this article, the changes of priorities and characteristics of American Presidentialism were analyzed, which are strongly connected with the changes in the political and cultural traditions of American society. Presidentialism is presented as a complex phenomenon in our study, that means not only the personalities and leaders of the country but also other systemic components, such as norms and principles, communicative, political and cultural factors, etc. The phenomenon of the representation of American political culture evolution was studied based on this holistic approach to Presidentialism – one of the fundamental U.S. institutions. Our research is supposed to observe on the changing priorities and features of the U.S. Presidentialism, taking into consideration the political culture evolutionism of the American society within its historical span. This enables to detect the USA alterations throughout the centuries identifying its political intentions and placing novelty values in political culture in case of the latter appearance since the epoch of the Founding Fathers. The article demonstrates that the inaugural addresses of American presidents reflect the evolution of American political culture, which has an impact on the further development of the institution of the presidency in the U.S. The research was conducted, using systems analysis. Structural-functional, institutional and communicative methods were used in the research. The empirical part of the research is based on content analysis of the presidential inaugural addresses, which proved the stability of the American participant civic culture traditions.

Amerika Birleşik Devletleri, benzeri görülmemiş bir tarihe ve liderlik politikasına sahip, dünya çapında görülmesi gereken bir ülkedir. ABD'nin geniş problem çözme, küresel çatışmaların üstesinden gelme, koalisyonlar kurma ve dünyanın gündemini belirleme konusundaki etkisi çığır açıcıdır. Bununla birlikte, ülke karşılaştığı birçok zorluğa rağmen, her zaman üst düzey bir dış pozisyon elde etmeyi ve siyasi iç dengesini korumayı başardı. Araştırma, on Amerikan başkanının (G. Washington, J. Monroe, JK Polk, A. Lincoln, W. Wilson, FD Roosevelt, JF Kennedy, R. Reagan, B. Obama ve D. Trump) göreve başlama konuşmalarını analiz ederek Amerikan siyasi kültürünün özünü belirlemeyi ve ABD tarihi boyunca kilit noktaların izini sürmeyi amaçlamaktadır. Başkanlık terimleri, önemli olayların Amerika Birleşik Devletleri'nde gerçekleştiği Amerikan tarihsel sürecinin farklı dönemlerini yansıtmaktadır. Bu makalede, Amerikan toplumunun siyasi ve kültürel geleneklerindeki değişikliklerle güçlü bir şekilde bağlantılı olan Amerikan Başkanlık sisteminin öncelikleri ve özelliklerindeki değişiklikler analiz edilmiştir. Çalışmamızda başkanlık, sadece ülkenin şahsiyetlerini ve liderlerini değil, aynı zamanda normlar ve ilkeler, iletişimsel, politik ve kültürel faktörler vb. diğer sistemik bileşenleri de ifade eden karmaşık bir fenomen olarak sunulmaktadır. Siyasi kültürün evrimi, ABD'nin temel kurumlarından biri olan Başkanlık sistemi bu bütünsel yaklaşım temelinde incelendi. Araştırmamız, Amerikan toplumunun siyasi kültür evrimciliğini tarihsel süreci içinde göz önünde bulundurarak, ABD Başkanlık sisteminin değişen önceliklerini ve özelliklerini gözlemlemeyi amaçlamaktadır. Bu, ABD'nin yüzyıllar boyunca siyasi niyetlerini belirleyen ve Kurucu Atalar döneminden bu yana ortaya çıkması durumunda siyasi kültüre yenilik değerleri yerleştiren değişimlerini tespit etmeyi sağlar. Makale, Amerikan başkanlarının açılış konuşmalarının, ABD'deki başkanlık kurumunun daha da geliştirilmesi üzerinde etkisi olan Amerikan siyasi kültürünün evrimini yansıttığını göstermektedir. Araştırma sistem analizi kullanılarak yapılmıştır. Araştırmada yapısal-işlevsel, kurumsal ve iletişimsel yöntemler kullanılmıştır. Araştırmanın ampirik kısmı, Amerikan katılımcı sivil kültür geleneklerinin istikrarını kanıtlayan başkanlık açılış konuşmalarının içerik analizine dayanmaktadır.
Amerikan Siyasi Kültür Evriminin Temsili Olarak ABD Başkanlığı